The rock in my throat - Yang, Kao Kalia, 1980- (Carolrhoda Books, 2024)
"In this moving true story, Kao Kalia Yang shares her experiences as a Hmong refugee child navigating life at home and school in America while carrying the weight of her selective mutism"--